The Philippine sugar industry a case study in government control - Poblador, Niceto S. (1964)
The sugar industry is unquestionably one of the most heavily regulated industries in the Philippines. Considering that sugar is one of the Philippines' largest export industries, the effects of its regulation have far-reaching socio-economic implications. This paper attempts to show how some aspects of the control of the sugar industry are mainly responsible for the relatively high cost of sugar production in the Philippines. Specifically, it will attempt to show how the present method of allocating domestic and export sugar quotas among the various planters and millers results in higher factor costs both in the farming and milling stages of production.
Includes bibliographical references.